What champions think: optimal attentional strategies for 2000m rowing - Lloyd, M.; Terry, P. C. (2006 Joint Conference of the Australian Psychological Society and the New Zealand Psychological Society, 26-30 Sept 2006, Auckland, New Zealand., 2006)
It is generally acknowledged within the rowing community that thought processes are closely linked to performance. The present study investigated the attentional routines of six male and four female rowers, all of whom were Olympic or World Championship medallists, or had a top-3 world ranking on the Concept II rowing ergometer. Participants responded to a range of questions about the attentional straegies they used during warm-up for, and when performing, a 2000m ergometer test, which is a regular activity for elite rowers and forms the basis for selection to international crews. Results showed that all respondents tended to segment their race into smaller blocks, based around distance or an equivalent number of strokes, with specific attentional cues used for different blocks. Pre-race strategies tended to emphasise maintaining mental and physical relaxation, focusing on key aspects of technique, and identifying target and split times. In-race attentional strategies emphasised cues such as fast start, counting strokes, focusing on breathing, technique and rhythm, positive self-talk, pain management, and maintenance of a positive mindset throughout the race. The present results will inform a follow-up study to test the efficacy of an optimum routine in a controlled environment.